Students’ Perceptions on the Effectiveness of Drilling in Improving Speaking Skills - Qurinta Shinta (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Speaking is one of the essential skills in English language learning because it enables learners to communicate their ideas, opinions, and feelings effectively. However, many English as a Foreign Language (EFL) students experience difficulties in speaking due to limited vocabulary, poor pronunciation, lack of confidence, and anxiety. One teaching technique that has been widely applied to overcome these problems is the drilling technique, which provides students with repeated opportunities to practice language forms. This study aims to investigate students’ perceptions on the effectiveness of drilling to improve speaking skills. The study employs a quantitative descriptive approach using open-ended questionnaires distributed to 44 students of Electrical Engineering taking conversation class. The questionnaire is used to measure students' perceptions regarding four aspects of the effectiveness of drilling on speaking skills: pronunciation accuracy, speaking fluency, vocabulary retention, and speaking confidence. The data were analyzed using descriptive statistics, including means, percentages, categories, and positive responses. The mean interpretation categories are determined based on a five-category Likert scale range, namely:1.00–1.80: very low,1.81–2.60: low, 2.61–3.40: moderate, 3.41–4.20: high, 4.21–5.00: very high. The results of the descriptive statistical analysis indicate that the perceptions of Electrical Engineering Class A students regarding the effectiveness of using drilling to improve speaking skills fall within the high to very high range.